Analysis of Post Episiotomy Nursing Care with Cold Compress Intervention - Nurafita, Hera; Yekti Widadi, Sri; Puspita, Tantri; Wahyudin (CV. Literasi Publikasi Indonesia, 2024)
Postpartum is the time to start after placenta birth until return of reproductive organs to in normal condition or before pregnancy taking place for 6-8 weeks. Service postpartum given to Mother during period from 6 hours to 42 days, because often give rise to rips in the road birth (episiotomy) which can give rise to happen bleeding and infection in the mother postpartum. The objective was to get an idea of the application of therapy compress cold as intervention in patients postpartum spontaneous with problem inconvenience post-partum. A descriptive case study using anamnesis, observation, physical examination, and medical records. The results showed that the case study of post-partum patients spontaneous with discomfort nursing problems post-partum consequence wound episiotomy obtained subjective data and objective data , author​ get problem nursing main inconvenience post-partum intercourse with perineal trauma during labor and birth , proven with exists wound episiotomy degree II . Discomfort caused by injuries​ episiotomy can overcome with use therapy compress cold, this be marked with exists decline scale painful from 5 to 2 after done intervention in 3 days. Therapy compress cold own significant influence​ of postpartum discomfort in post-partum patients spontaneous Birth